ANALISIS ENDAPAN SEDIMEN DASAR BENDUNG KAMUN TERHADAP TINGGI MERCU DAN KEHILANGAN DEBIT AIR SALURAN INDUK CILUTUNG BARAT KABUPATEN MAJALENGKA - Lumban Toruan, Erni Sari; Rijaluddin, Arief; Dian Heryadiana, Asep; Sunarya, Yoyo (J-ENSITEC, 2024)
Kamun Dam is a permanent weir with its water intake in the Cilutung River Basin (DAS). One major factor affecting water reduction at the weir is sediment settling at the upstream base. Effective and efficient management is crucial for irrigation water and networks to maximize benefits. Water loss from primary to secondary and tertiary channels negatively impacts irrigation system performance. The water flow through weirs and structures with varying discharges influences the water surface profile and its characteristics.This research aimed to determine the water level, total sediment transport capacity, water discharge loss in the West Cilutung main channel, and the water surface profile shape. The data comprised primary data from field investigations and secondary data, including average discharge data from 2008-2017.Water level analysis was performed using hydraulic formulas and the Trial and Error method. The highest water level recorded was 0.74 m in April, and the lowest was 0.22 m in August. Sediment transport analysis, using the Meyer-Peter Muller method, estimated that it would take approximately 13 years to fill the upstream of Kamun Dam with 1,436,470.04 m³ of sediment, without dredging, given a river width of 74.15 m and height of 3 m. Water discharge loss analysis, using the inflow and outflow method, showed Qrenc results from BLK.1-BLB.1 at 0.06 m³/sec and Qactual at 0.27 m³/sec. The water surface profile analysis, using the graphical integration method, yielded Qrenc results for profile I f(y) = 4786 and Qactual results for profile I f(y) = 789